Big breath in - Straley, John, 1953- (Soho Crime, 2024)
"This new stand-alone from the former Writer Laureate of Alaska and author of the acclaimed Cecil Younger series introduces an amateur sleuth with an ax to grind-and a child to save. Diagnosed with terminal cancer, retired marine biologist Delphine is on the brink of throwing in the towel. She has outlived her PI husband and feels like a burden to her son and his growing family. One night, while contemplating how to go on, Delphine witnesses a woman and her young child being victimized by her apparent boyfriend. When Delphine later discovers the woman has gone missing, she embarks on a quest to track her down and help her and the child. What begins as a chance encounter balloons into an at-once zany and heartfelt rescue mission across the Pacific Northwest. Along the way, Delphine encounters the dregs of humanity-grappling with schemers, kidnappers, and murderers-as well as its joys. With the help of a few friends, a retired PI, and a queer biker gang, Delphine becomes determined to stop the bad guys from getting away with it . . . knowing full well it may be her last hurrah. While Big Breath In stands alone, longtime Straley fans will recognize the characteristic wit, heart, and contemplation of life that threads through every one of his books-and discover a new heroine to fall in love with"--